Beyond Dilution: Quantum Insights into the Mystery of Homeopathic Remedies (Homoeopathy for All, 2025)
The science of Homeopathy is  beyond the contemporary sciences.  As mentioned by Dr. Stuart Close  in his philosophy, “By mechanical  dilution and potentiation poisons  may be deprived of their lethal  qualities and transformed into  healing remedies normally  assimilable by the sick organism”.  This involves using ultra-diluted  substances to stimulate the body  during illness. He discussed  concepts from Physics, Biology, and  Mathematics, such as the Theory  of Infinitesimals, Electromagnetic  Induction, and Ionisation, etc
Keywords: mechanisms